Engagement in perinatal depression treatment: a qualitative study of barriers across and within racial/ethnic groups - Esti Iturralde; Crystal A. Hsiao; Linda Nkemere; Ai Kubo; Stacy A. Sterling; Tracy Flanagan; Lyndsay A. Avalos (BMC, 2021)
Abstract Background To better understand previously observed racial/ethnic disparities in perinatal depression treatment rates we examined care engagement factors across and within race/ethnicity. Methods Obstetric patients and women's health clinician experts from a large healthcare system participated in this qualitative study. We conducted focus groups with 30 pregnant or postpartum women of Asian, Black, Latina, and White race/ethnicity with positive depression screens. Nine clinician experts in perinatal depression (obstetric, mental health, and primary care providers) were interviewed. A semi-structured format elicited treatment barriers, cultural factors, and helpful strategies. Discussion transcripts were coded using a general inductive approach with themes mapped to the Capability-Opportunity-Motivation-Behavior (COM-B) theoretical framework. Results Treatment barriers included social stigma, difficulties recognizing one's own depression, low understanding of treatment options, and lack of time for treatment. Distinct factors emerged for non-White women including culturally specific messages discouraging treatment, low social support, trauma history, and difficulty taking time off from work for treatment. Clinician factors included knowledge and skill handling perinatal depression, cultural competencies, and language barriers. Participants recommended better integration of mental health treatment with obstetric care, greater treatment convenience (e.g., telemedicine), and programmatic attention to cultural factors and social determinants of health. Conclusions Women from diverse backgrounds with perinatal depression encounter individual-level, social, and clinician-related barriers to treatment engagement, necessitating care strategies that reduce stigma, offer convenience, and attend to cultural and economic factors. Our findings suggest the importance of intervention and policy approaches effecting change at multiple levels to increase perinatal depression treatment engagement.